Production of Bioethanol from Bore (Alocasia macrorrhiza) - Díaz Díaz, Elkin Darío; Quinto Solis, Salma Rosa (Ingeniería Solidaria, 2019)
Introduction: This publication is the product of research entitled “Production of Bioethanol from Bore” developed in the year 2016 at the National University of Colombia in Medellín, Colombia.Objective: To reduce the emissions of gases produced by the combustion of petrol by use of a 90:10 fuel-ethanol mixture from the bioethanol obtained from the Bore plant (Alocasia macrorrhiza).Methodology: The process for obtaining ethanol involves pretreatment of the raw material through washing and husking, liquefied, pre-drying, pre-shredding, drying, crushing and sifting and later a microbial fermentation using the Yeast Saccharomyces cerevisiae.Conclusions: The admixtures of bioethanol in 90:10 fuel-bioethanol mixtures generated an increase in the quality of the fuel, due to the oxygen present in the mixture which improves the combustion. Following this work, it is concluded that Bore (Alocasia macrorrhiza) is a promising raw material in the production of a bioethanol with the highest concentrations of starch and better results from fermentation with Saccharomyces cerevisiae.Originality: To provide a new unknown raw material to produce a bioethanol destined for mixtures with gasoline.Limitations: The general lack of knowledge of the plant, commonly called a weed, in addition to few references related to its use in the production of bioethanol.
Keywords: Bioethanol; Bore; Fermentation; Pretreatment; Global warming